Characterization and antitumor activities of a water-soluble polysaccharide from Ampelopsis megalophylla. (20th September 2015) - Xie, Xianfei; Wang, Jianwu; Zhang, Hanping
Highlights: The leaves of Ampelopsis megalophylla are traditional herbal medicines in China. A polysaccharide (AMP) was purified from A. megalophylla. AMP effectively inhibits the tumor growth in S180 tumor-bearing mice. The antitumor effect of AMP is associated with its potent immunostimulatory activity. AMP has a potential for development as an adjuvant for chemotherapy drugs. Abstract: A water-soluble polysaccharide named as AMP was isolated and purified from the leaves of Ampelopsis megalophylla by DEAE-52 Cellulose and Sephadex G-100 column chromatography. AMP had an average molecular weight of about 8.4 × 10 4 Da and was composed of galactose (Gal), mannose (Man), glucose (Glc), arabinose (Ara), and rhamnose (Rha) in a molar ratio of 2.7:1.6:1.1:0.6:0.3. After 10 days of AMP (50, 100, and 200 mg/kg) treatment once daily in tumor-bearing mice, AMP oral administration could inhibit the growth of transplantable Sarcoma 180 (S180) tumor in mice and increase the spleen index and body weight. Furthermore, AMP also promote splenocytes' proliferation induced by concanavalin A (ConA) and lipopolysaccharide (LPS), strengthen peritoneal macrophages to devour neutral red and increase the production of interleukin-2 (IL-2), tumor necrosis factor-alpha (TNF-α), and interferon-gamma (IFN-γ) in serum. These results suggest that AMP had clear antitumor activity, which might be related to its regulation of immune function in mice.